Influence of Genetic Variation in Oak Leaf Roller Pupae and Their Host Plants on Body Sizes of Their Parasitoids, Itoplectis maculator (Fabricius, 1775) - Andrey Simchuk; Anatoly Ivashov (Psyche: A Journal of Entomology)
Variation in sizes of parasitoids Itoplectis maculator F. (Hymenoptera, Ichneumonidae) were studied in respect to their genetic variation as well as to the genetic variations in their host insect (Tortrix viridana L.) pupae and their host plant (Quercus pubescens Willd). The data obtained have shown that the interactions between genotypes of parasitoids and their host insects contribute up to 49%, and interaction between genotypes of parasitoids and oaks contributes up to 28% to the total variation in the parasitoid body sizes. As the parasitoid body size is fitness related, we may conclude that fitness of a parasitoid depends on not only its genotype but also on genotypes of its host insects and even the tree on which the host insects have developed. As a result the genotypes of representatives of the studied food chain links were found to be stochastically associated.